Fixation of potassium in some soils of the subhumid zone of Nigeria - Tening, A.S.; Omueti, J.A.I.; Tarawali, G. (Informa UK Limited, 1995)
Studies of potassium (K) fixation in the soil were conducted by evaluating the effect of applied K on the extractability of K with time. A series of five K-sorption treatment solutions, 0.11, 0.22, 0.45, 0.90, and 1.80 cmol/kg were prepared and applied as potassium chloride (KC1) to three sets of soils. The first set of soil samples was extracted with one normal ammonium acetate (1N NH4OAc) extractant for K after one day of incubation. The second and third sets were extracted with the same extractant after seven and 42 days of incubation, respectively. The amount of K fixed was determined. Correlation between applied K and K fixed was carried out. The mean proportion of K fixed ranged from 0 in soils from Kurmin Biri to 55 percent in soils from Funafuna upon addition of 0.11 cmol k/kg. While fixation increased with increase in the concentration of added K, there was no linear relationship between the proportion of K fixed and the amount added at higher incubation periods. Potassium recovered also increased with added K in all the incubation periods with the 42-day period having the highest amount of K recovered. Potassium added was highly correlated (P<0.01) with K fixed during all the incubation periods.